2018
DOI: 10.5296/ijafr.v8i1.12824
|View full text |Cite
|
Sign up to set email alerts
|

CEO Characteristics and Valuation of the Organization: A Quantile Regression Analysis

Abstract: This study examines the effects of three highly-visible CEO characteristics on a valuation of the organization. Using a sample for Chinese firms over the period of 2007-2016, we find that CEO age is consistently related with lower organizations' valuation. CEO tenure is also related with lower valuation, but more significantly so in the higher quantiles of organizations'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Also, longer tenure of the CEOs enhances their accountability and inculcate a sense of ownership in them, which helps them in aligning Gupta & Mahakud, 2020). However, the finding is consistent with the studies by Mansoor, Ellahi, Khan, andRahman (2017), andPeni (2014); who found that CEOs with long tenure have significant positive effect on firms' performance than short-tenured CEOs while it contradicts tudies by Nazir, Nazir, and Khan (2018), Nguyen, Miloud, and Zhao (2017), and Barka and Legendre (2016) who found that CEO tenure has significant negative effect on firms' performance.…”
Section: Tablesupporting
confidence: 89%
See 2 more Smart Citations
“…Also, longer tenure of the CEOs enhances their accountability and inculcate a sense of ownership in them, which helps them in aligning Gupta & Mahakud, 2020). However, the finding is consistent with the studies by Mansoor, Ellahi, Khan, andRahman (2017), andPeni (2014); who found that CEOs with long tenure have significant positive effect on firms' performance than short-tenured CEOs while it contradicts tudies by Nazir, Nazir, and Khan (2018), Nguyen, Miloud, and Zhao (2017), and Barka and Legendre (2016) who found that CEO tenure has significant negative effect on firms' performance.…”
Section: Tablesupporting
confidence: 89%
“…Younger CEOs are also described as making more and riskier financing decisions (Serfling, 2014). Therefore, studies by Meltschakow (2020), Kokeno and Muturi (2016), Yasser, Al-Mamun, and Suriya, (2014) found that CEO age has significant positive effect on firms' performance while Studies by Nguyen, Miloud, and Zhao (2017), Nazir, Nazir, andKhan (2018), andDiks (2016), found that CEO age has significant negative effect on firms' performance. Studides by Razali, Azmi, Hwang, and Lunyai (2022), Poole (2016) and Cornet, Marcus, Saunders and Tehranian (2012) found that CEO Age has nonsignificant effect on the firm performance.…”
Section: Ceo Age and Performance Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a CEO greatly influences the company's reputation (Chiu, Li, and Kao 2022). Therefore, this position must be filled by selected people (Nazir et al 2018). The CEO plays an active role in decision-making and acts as a point of communication between the board of directors and shareholders.…”
Section: Introductionmentioning
confidence: 99%
“…The CEO plays an active role in decision-making and acts as a point of communication between the board of directors and shareholders. Leadership is a fundamental ability that must be owned by every CEO, even for the manager class (Nazir et al 2018). This leadership ability is closely related to the CEO's position as the company's leader (Chiu et al 2021).…”
Section: Introductionmentioning
confidence: 99%